Chemical constituents and antimicrobial properties of the volatile oil from the rind of Citrus hystrix De Candolle var. torosa (Blanco) Wester (Family Rutaceae) - Lozano, Araceli Mondragon
The fresh rind of Citrus hystrix D.C. var. torosa (Blanco) Wester, family Rutaceae, yielded 3.22% on a wet basis, of a colorless essential oil obtained by steam distillation. Studies on its physicochemical properties gave the following results: refractive indec at 25(degrees C) is 1.4675; specific gravity at 30(degrees C) is 0.8517; specific rotation at 30(degrees C) is +26.70(degrees C); and aldehyde content is 37.97% calculated as citronellal. The oil was completely miscible in 90-95% alcohol, slightly miscible in 70-80% alcohol and immiscible in 50-60% alcohol. Thin layer chromatography of the oil showed the presence of four major components which are limonene, beta-pinene, camphene and possibly citral. Gas chromatography combined with mass spectrometry confirmed the presence of limonene, beta-pinene, alpha-pinene, camphene, and citronellal and the absence of citral. The oil was found to be active against Fusarium moniliforme, Microsporum canis, Sarcina lutea, Candida albicans, Bacillus cereus, Bacillus subtilis, Micrococcus aureus, Escherichia coli, but negligible with Pseudomonas aeruginosa. Comparison of kolobot oil with known antifungals showed that it is more active than griseofulvin, ketoconazole and mycostatin at the same concentration.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines Manila, April 1993.
Keywords: Rutaceae